Content Advertising Assistance through Instagram Ads in the Kampung Wisata Tridi - Dani Riyadi; Angga Eka Alfianto; Ayu Siti Ni'mah Syuridinia; Mulyono Mulyono (Trescode Green Organization, 2023)
This study aimed to enhance content advertising for Kampung Wisata Tridi through Instagram Ads. It involved a two-phase approach: a needs assessment and an intervention. The assessment uncovered a limited understanding of Instagram Ads among Kampung Wisata Tridi members. The intervention comprised a training session attended by 10 representatives. Results indicated improved comprehension of Instagram Ads basics and effective usage. Post-training, participants successfully created and managed their Instagram Ads. Conclusively, the study highlighted Instagram Ads as a valuable tool for promoting tourism destinations. The training session equipped Kampung Wisata Tridi with essential knowledge and skills, enabling them to leverage Instagram Ads for reaching a broader audience in their content advertising efforts.